Efficient Profile Matching Methods Using Convolution Neural Networks - Dr. S. Siamala Devi, Thiraimathi S, Sriabirami R,Sinega V (International Journal of Advanced Science and Technology, 2020)
Background: Biometrics are physical or behavioral human characteristics to that can be used to digitally identify a person to grant access to systems, devices or data. Face recognition can be a concept of biometric for safety approach. A profile describes a collection of properties, e.g. a group of abilities a person may additionally have, or a collection of talents a cricketer can also have with regard to a particular group strategy. Findings: The methodologies like Cascade Classifier and Convolution Neural Network are applied to detect face of a private. A comparison has been made among the above-mentioned methodologies and  therefore the inferred result shows that Convolution Neural Network has produced a far better performance. Therefore, CNN helps the input image to be matched with the profile in an efficient way.